2022
DOI: 10.3390/cancers14174243
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Multiparametric Quantitative Magnetic Resonance Imaging Correlates with Prognosis and Recurrence Patterns in Pancreatic Ductal Adenocarcinoma

Abstract: Magnetic resonance imaging (MRI) has been shown to be associated with prognosis in some tumors; however, the correlation in pancreatic ductal adenocarcinoma (PDAC) remains inconclusive. In this retrospective study, we ultimately included 136 patients and analyzed quantitative MRI parameters that are associated with prognosis and recurrence patterns in PDAC using survival analysis and competing risks models; all the patients have been operated on with histopathology and immunohistochemical staining for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This exacerbates the degree of barrier destruction and so the proportion of extracellular space outside the blood vessels and, consequently, V e increase. This is believed to be the reason for the link between poor prognosis and high V e values[ 22 , 23 ]. In a study on dynamic contrast enhanced-MRI quantitative parameters for predicting the efficacy of concurrent chemoradiotherapy for locally advanced cancer, Liu et al [ 24 ] discovered tumor regression when V e was low, which could be used as a potential indicator to predict the treatment response of locally advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This exacerbates the degree of barrier destruction and so the proportion of extracellular space outside the blood vessels and, consequently, V e increase. This is believed to be the reason for the link between poor prognosis and high V e values[ 22 , 23 ]. In a study on dynamic contrast enhanced-MRI quantitative parameters for predicting the efficacy of concurrent chemoradiotherapy for locally advanced cancer, Liu et al [ 24 ] discovered tumor regression when V e was low, which could be used as a potential indicator to predict the treatment response of locally advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the D value primarily re ects the density of tumor cells, with lower values representing higher cell density, more active proliferation and poorer differentiation [8]. Therefore a lower D value predicts a higher risk of recurrence and a poorer prognosis, as has also been demonstrated in nasopharyngeal and pancreatic cancers [30][31]. Meanwhile, Qu [31] found that D values were negatively correlated with alphasmooth muscle actin (α-SMA) and hypoxia-inducible factors (HIFs) expression in pancreatic cancer, suggesting that D values may be closely related to broblast activation, angiogenesis and microenvironmental hypoxia in tumors, thus revealing the malignancy and treatment resistance of cancers.…”
Section: Discussionmentioning
confidence: 99%